Respuesta :

Answer:

  c.  S'(3, 1), T'(1, -1), U'(0, 1)

Step-by-step explanation:

Reflection across the y-axis negates the x-coordinate, so is equivalent to the transformation ...

  (x, y) ⇒ (-x, y)

Reflection across the horizontal line y=c is equivalent to the transformation ...

  (x, y) ⇒ (x, 2c-y)

So, the combined reflections are equivalent to the transformation ...

  (x, y) ⇒ (-x, 4 -y)

Then we have ...

  S(-3, 3) ⇒ S'(-(-3), 4-3) = S'(3, 1)

  T(-1, 5) ⇒ T'(-(-1), 4-5) = T'(1, -1)

  U(0, 3) ⇒ U'(-(0), 4-3) = U'(0, 1) . . . . matches choice C